ENVIRONMENTALLY FRIENDLY AND SUSTAINABLE FISHERIES CATCH SKIPJACK TUNA (Katsuwonus pelamis Linneus) IN TOMINI BAY, GORONTALO PROVINCE. - Syamsuddin; Lis M Yapanto; Achmar Mallawa; Farid Th. Musa (International Journal on Integrated Education, 2022)
Environmentally Friendly and Sustainable Catching Fishery of Skipjack (Katsuwonus pelamis Linneus) In Tomini Bay, Gorontalo Province. This study aims to analyze environmentally friendly technology and sustainability of skipjack tuna (Katsuwonus pelamis Linneus). This research was carried out from March 2021 to September 2021 in the waters of the Gulf. Tomini Gorontalo Province. Data were collected through surveys, interviews and questionnaires. Environmentally friendly aspects were analyzed using the value function of Monintja (2000), and Mallawa et al.,(2006). The results of this study indicate that the fishing gear, tug line, hand line, purse seine, and payang are considered environmentally friendly, respectively.